Effect of Cytokines On The In Vitro of Sweet Kaffir Lime (Citrus hystrix Dc) - Handayani, Rd. Selvy; Yunus, Ismadi; Tillah, Nadia; Handayani, Ira (Yayasan Pertanian Tropika Indonesia (YPTI), 2020)
Sweet kaffir lime (Citrus hystrix Dc), also called